Respuesta :

Answer:

Solving the equation : [tex]y+\frac{y}{a}=b\:if\:a\neq\: -1[/tex]  for y we get [tex]\mathbf{y= \frac{ab}{a+1},\:if\:a\neq -1}[/tex]

Step-by-step explanation:

We need to solve for y the equation: [tex]y+\frac{y}{a}=b\:if\:a\neq\: -1[/tex]

We need to find value of y

Solving:

[tex]y+\frac{y}{a}=b[/tex]

Taking LCM of a, 1 we get a

[tex]\frac{a*y+y}{a}=b\\\frac{ay+y}{a}=b[/tex]

Multiply both sides by a, a will be cancelled on left side

[tex]a(\frac{ay+y}{a})=ab\\ay+y=ab[/tex]

Taking y common from left side:

[tex]y(a+1)=ab[/tex]

Divide both sides by a+1

[tex]\frac{y(a+1)}{a+1}=\frac{ab}{a+1}\\y= \frac{ab}{a+1},\:if\:a\neq -1[/tex]

So, Solving the equation : [tex]y+\frac{y}{a}=b\:if\:a\neq\: -1[/tex]  for y we get [tex]\mathbf{y= \frac{ab}{a+1},\:if\:a\neq -1}[/tex]

ACCESS MORE